Factors Associated With Efficacy of Cognitive Behavior Therapy vs Education for Patients With Irritable Bowel Syndrome - Lackner, Jeffrey M. (Clin Gastroenterol Hepatol, 2018)
BACKGROUND & AIMS: Among patients with irritable bowel syndrome (IBS), it would be helpful to identify those most likely to respond to specific treatments, yet few factors have been identified that reliably predict positive outcome. We sought to identify pretreatment baseline characteristics that associate with symptom improvement in patients who received empirically validated regimens of cognitive behavior therapy (CBT) or IBS education. METHODS: We analyzed data from the IBS Outcome Study, in which 436 patients with IBS (average age, 41 years; 80% female) were randomly assigned to groups that received to 4 or 10 weeks of cognitive behavior therapy or education. Baseline data were collected from all participants on sociodemographic and clinical features and comorbidities. Interaction analyses used a modified linear probability model with Huber-White robust estimators to identify baseline factors that moderated as a function of treatment condition symptom improvement based on the IBS-version of the Clinical Global Impressions-Improvement Scale. RESULTS: Whether the primary outcome of IBS symptom improvement was rated by patients or physician assessors blind to treatment 2 weeks after it ended, higher percentages of patients had symptom improvement after CBT compared with EDU among those with low levels of trait anxiety (71.3% vs 34.9%; P<.05) or anxiety sensitivity (71.7% vs 38.6%; P<.05) and for those with baseline typical levels of trait anxiety (66.0% vs 47.1%; P<.05) or anxiety sensitivity (66.3% vs 47.1%; P<.05). For patients with high trait anxiety or anxiety sensitivity, the difference in percentage of responders to CBT vs EDU was non-significant for trait anxiety (60.6% vs 59.2%) and anxiety sensitivity (60.9% vs 55.9%). If patients scored at or below 22 on the Trait Anxiety Inventory, CBT had a statistically significant advantage over EDU. If patients scored at or below 29 on the Anxiety Sensitivity Inventory, there was a statistically significant advantage for CBT vs EDU. CONCLUSION: In analyses of outcomes of patients with treatment-refractory IBS, baseline levels of trait anxiety and anxiety sensitivity (fear of arousal symptoms) were associated with improved gastrointestinal symptoms following CBT compared to IBS education. These findings and approaches might be used to optimize selection of treatment for patients with IBS.